2022
DOI: 10.1039/d2ta00550f
|View full text |Cite
|
Sign up to set email alerts
|

Atomic bridging modulation of Ir–N, S co-doped MXene for accelerating hydrogen evolution

Abstract: Two-dimensional Ti3C2Tx MXenes have attracted significant interests as low-cost supports to anchor single atoms owing to their unique properties. Nevertheless, there is still lack systematic investigation on the coordinative interaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…For example, Tan and colleagues anchored Ir atoms on heteroatom N, S co-doped Ti 3 C 2 T x . 127 The theoretical calculation results showed that the N and S co-doped Ti 3 C 2 T x support can capture electrons from the Ir single atom and redistribute the charge in the interface region of the Ti 3 C 2 T x support, and thus IrSA–2NS–Ti 3 C 2 T x exhibited significant HER catalytic activity in both acidic and alkaline solutions.…”
Section: Strategies To Enhance the Electrocatalytic Performance Of No...mentioning
confidence: 96%
“…For example, Tan and colleagues anchored Ir atoms on heteroatom N, S co-doped Ti 3 C 2 T x . 127 The theoretical calculation results showed that the N and S co-doped Ti 3 C 2 T x support can capture electrons from the Ir single atom and redistribute the charge in the interface region of the Ti 3 C 2 T x support, and thus IrSA–2NS–Ti 3 C 2 T x exhibited significant HER catalytic activity in both acidic and alkaline solutions.…”
Section: Strategies To Enhance the Electrocatalytic Performance Of No...mentioning
confidence: 96%
“…[191] Metal carbides can also be easily modified by anion atoms due to their changeable surface chemical groups. [192][193][194] Tan et al reported the single Pt atoms supported by 3D porous N, P co-doped Ti 3 C 2 T x MXene (PNPM) nanosheets prepared by a gelation-and-pyrolysis method (Figure 11d-f). [192] Due to Pt atoms being coordinated with N(O) and P atoms, the valence state of Pt was higher than that of Pt nanoparticles loaded on PNPM (Figure 11g-i), which arose from the strong electronic interactions between Pt atoms and PNPM nanosheets.…”
Section: Metal Carbidesmentioning
confidence: 99%
“…The fitting FT-EXAFS spectrum of Pt L 3 -edge presented a Pt-N(O) coordination number of 3 and a Pt-P coordination number of 1.1 for Pt 1 /PNPM (Figure 11j), thus leading to Pt atom being of +1.82, thereby resulting in a comparable HER performance to Pt/C (20 wt%, Pt) in acidic and alkaline media at a low loading amount of 2.32 wt% Pt. Similarly, N and S dopants can also coordinate single metal atoms to tune electronic states leading to optimization of hydrogen adsorption, e.g., Ir 1 /N and S codoped Ti 3 C 2 T x , [193] Ru 1 /N and S co-doped Ti 3 C 2 T x , [194] Ru 1 /N doped Ti 3 C 2 T x . [195] These non-metallic atoms doped metal carbides-based SACs exhibit enhanced electrocatalytic activities, owing to their differences in electronegativity compared to C and O atoms.…”
Section: Metal Carbidesmentioning
confidence: 99%
“…11,12 Ti-based MXenes, especially Ti 3 C 2 , are the most commonly used MXenes, but their application in the field of HER is limited by excessive overpotential. 13,14 Fortunately, many studies have shown that Mo-based MXenes have great potential for application in the HER field. [15][16][17][18] Such as, the research of Zhi et al showed that Mo-based MXenes effectively avoided the toxic effect of the F-terminal group on the HER due to the weak Mo-F bond, so they had lower overpotential than Ti-based MXenes and showed better HER performance.…”
Section: Introductionmentioning
confidence: 99%